Contrasting ecological regimes of microbial plankton along beagle channel and burdwood bank in sub-antarctic waters - Guinder, Valeria Ana; Malits, Andrea; Ferronato, Carola; Krock, Bernd; Garzon Cardona, John Edison; Martinez, Ana M.
Marine microbial plankton hold high structuraland functional diversity, however, high-resolution data are lacking in a largepart of the Global Ocean. The Burdwood Bank (BB) hosts rich benthicbiodiversity in low chlorophyll waters of the southern Patagonian Shelf,Argentina. So far, the microorganisms that sustain the productivity over thebank have not been described. During austral summer 2016, we assessed themicrobial plankton (0.2-200 µm cell size) diversity and biomass along alongitudinal transect (54.2-55.3°S, 58-68°W) from the Beagle Channel (BC) tothe BB, characterized by contrasting hydrography. Results displayed a markedzonation in the composition and structure of the microbial communities.Protistan phytoplankton biomass was 28 times higher in the BC than in oceanicwaters above the BB, attributed mainly to large diatom blooms. In contrast,over the BB, small coccolithophores such as Emilianiahuxleyi, nanoflagellates and phototrophic picoplankton dominated. In turn,the biomass of microheterotrophs above the BB doubled the biomass in the BC dueto large ciliates and dinoflagellates. Notably, toxic phytoplankton species andtheir associated phycotoxins were detected, in particular high abundance of Dinophysis acuminata and pectenotoxinsabove the bank, highlighting their prevalence in open subpolar regions.Picoeukaryotes and Synechococcus wereremarkably important over the bank, both at surface and deep waters. Theirbiomass surpassed that of phototrophic protists by 5 times, emphasizing theimportance of small-sized phytoplankton in low chlorophyll waters. Thehomogeneous water column and high retention over the bank seem to favor thedevelopment of picophytoplankton and microzooplankton and their exportation tothe benthos. Overall, our findings unfold the plankton configuration in theSouthern Patagonian Shelf, ascribed as a sink for anthropogenic CO2,and highlight the diverse ecological traits that microorganisms develop toadjust their yield to changing conditions. Fil: Guinder, Valeria Ana. Consejo Nacional de ...